Efficient green phosphorescent tandem organic light emitting diodes with solution processable mixed hosts charge generating layer - Talik, N.A.; Yeoh, K.H.; Ng, C.Y.B.; Yap, B.K.; Woon, K.L. (Elsevier, 2014)
A novel solution processable charge generating layer (CGL) that consists of 1,4,5,8,9,11-hexaazatriphenylene hexacarbonitrile (HATCN6)/Poly(N-vinylcarbazole) (PVK): 1,1-bis-(4-bis(4-tolyl)-aminophenyl) cyclohexene (TAPC) for a tandem green phosphorescent organic light emitting diode (PHOLED) is demonstrated. The use of orthogonal solvent to dissolve HATCN6 and PVK:TAPC is the key to overcome the interface erosion problem for the solution processed CGL. The current efficiency of the 2 wt% TAPC mixed with PVK is the highest at 24.2 cd/A, which is more than three-folds higher than that of the single device at 1000 cd/m2.